Stoires of Experience On The Constitution Of Political Subjectivity - Caro, Angélica (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The article presents advances of the project Juan, which aim was to recognize elements that shape the political subjectivity of a multi-grade school teacher through an investigative and formative exercise in narrative writing. The work used a qualitative approach of hermeneutics-narrative type. From the perspective of narrative research, writing was an exercise of training that made it possible to build new horizons of meaning around practices. It presents advances of pedagogical practice from the elaboration and reworking of autobiographical stories. Two categories of analysis are structured: the political in the care of life and the critical distancing pre-established forms of being a teacher. Which made it possible to reflect on how training processes allow the configuration of political subjectivity through narratives of educational experiences.